Religion and Politics: Examining the Interplay and Impact - Kashif Lodhi; Dr. Atif khan; Gianfranco Rusconi; Sohail Ahmad (Corresponding Author) (Journal of Religion and Society, 2025)
This extensive article is painting out the complexity of religion political relations comparing the historical angles to the modern ones and the future ones. The historical research reveals long-standing relationships between religious ideas and political systems illustrated in the historical period of ancient societies and Middle Ages as well as in contemporary period. Religious changes that characterise historical transformations such as the Protestant Reformation and the Enlightenment era define the emerging pattern of religious politics. In the modern sense, this relationship is particularly diverse through the samples given by Haynes and Gomez with the example of how religious actors are actively involved in the global process. Knowledge from such studies as Smith and Martinez enlightens the subjugation of power between the religious organizations and the political authorities while explaining that religious organizations do play the role of initiating change within the society. Furthermore, the classroom analysis of cultural identity and nationalism shows religious contributions in the formation/disassembly of national discourses as discussed by Brown and Patel. The review examines the two-fold process of religion as a cause of conflict and as a potential source of peace, according to Fischer & Ahmad. The problems tied to discrimination of religions and the prospects of cooperative administration are examined while using the insights of such scholars as Yang and Mendelsohn. Taking a look at prospective future violent trends, the study makes predictions related to religious politics in the international level, advances in technology, and demography. Taking a cue from political science, sociology and religious studies, this study enhances a plural understanding of the interrelations between religion and politics as tangled. Thus, it can be escalated that even after ending this relationship has a far-stretched effects on the global legal framework, the cultures and humans on the whole. Keywords: Complexity, religion political relations, historical angles, modern ones, the historical period